Revealing the fireworks-set-off pattern of spatial multi-function expansion across cities leveraging big geodata – a case of the Greater Bay Area, China - Ku Gao; Xiaomei Yang; Zhihua Wang; Yueming Liu; Huifang Zhang; Xiaoliang Liu; Qingyang Zhang (International Journal of Digital Earth)
In monitoring of urban expansion, impervious surface data obtained via remote sensing can capture spatial details better compared to statistical data. Nevertheless, it lacks socio-economic function heterogeneity, making it still difficult to reveal the spatial multi-function expansion (SMFE) pattern. This hampers fine-scale collaborative planning of regional functions and human-land system, especially across cities. In this study, we mapped urban land use with fine functions leveraging big geodata for the Greater Bay Area (GBA), China, during 1980–2020, and identified across-cities SMFE pattern and its ecological effects. We found that (1) across-cities SMFE exhibited a fireworks-set-off pattern, including sprawling along river in the plains between coastal port cities and inland core cities and diffusing from inland core cities on the plains to inland node cities in the mountains; (2) social-living, business-trade, and industry-production functions were sequentially primary expanding functions; (3) paddy and forest were two major land cover types encroaching upon inland cities, while coastal cities primarily suffered from losses of water. In the future, planners should focus on ecological protection of hilly and coastal areas when formulating industrial transfer policies and enhancing transport networks. Our study contributes a new, cost-effective avenue for promoting collaborative across-cities function planning and sustainable human-land system.